Prevalence and Factors Associated With Obesity Among Children and Adolescents Living With Disability in Yaoundé, Cameroon - Enjeh Jabbossung Fombo; Nchinjoh Sangwe Clovis; Michael Ngenge Budzi; Marvel Changoh Changoh; Leslie Tasha Mbapah; Hawi Kidanu Kebede; Adam J. Rose (SAGE Open)
Obesity is a global health concern, with children and adolescents living with disabilities being particularly vulnerable. This study investigated the prevalence of obesity and identified associated factors among children and adolescents with disabilities in Yaoundé, Cameroon. A cross-sectional study was conducted, involving 135 children and adolescents with disabilities. Data on parent characteristics (e.g., age and household income) and child characteristics (e.g., sex and age) were collected through self-report questionnaires filled by parents. The children’s and adolescent’s weight (in Kg) and height (in m) were measured, and Body Mass Index (BMI) status calculated. Univariate and multivariate analyses were performed to examine the associations between these independent variables and obesity. A p -value of less than .05 was considered significant. The prevalence of obesity among children and adolescents with disabilities was 14% (95% CI: 8.1–19.9%). Increased meal frequency (OR = 4.2, 95% CI: 1.6–12.6, p  = .005) and experiencing emotional abuse (OR = 6.4, 95% CI: 1.2–41.8, p  = .03) were significantly associated with obesity on multivariable analysis. This study reveals a high prevalence of obesity among children and adolescents with disabilities in the Yaoundé, Cameroon. Higher daily meal frequency and a history of emotional abuse were associated with obesity. Our findings suggest that comprehensive interventions addressing dietary habits, psychosocial well-being, and inclusive environments are essential to prevent and manage obesity among children and adolescents with disabilities.